Complicações relacionadas à colheita do líquido cerebroespinhal e à hemilaminectomia associada à fenestração de disco intervertebral em cães - Schwab, Marcelo Luís (2023)
Cerebrospinal fluid (CSF) analysis is an auxiliary diagnostic test used in neurological routine and indicated in the suspicion of diseases in the central nervous system and in some cases in the peripheral nervous system. CSF can be performed in the cerebellomedullary and lumbar cisterns. In turn, the hemilaminectomy and intervertebral disc fenestration are surgical techniques used in the treatment of dogs with compressive myelopathy caused by intervertebral disc extrusion. These procedures are not risk-free, and knowledge of possible complications is extremely important to try to prevent them. Article 1 of this thesis reports two cases of dogs with a history of epileptic seizures that underwent spinal tap. After this procedure both developed progressive hemorrhagic myelomalacia, confirmed by histological study. As for article 2, a prospective study was developed to contribute to the surgical complications related to hemilaminectomy procedures and intervertebral disc fenestration in 64 dogs. In this study, complications were observed in 15.62% (n=10/64) of cases in one or more of the evaluated periods. Iatrogenic rhizotomy, access to the spinal canal contralateral to the lesion, and cardiorespiratory arrest were observed intraoperatively. Abdominal wall flaccidity, neurological worsening, hematoma, dehiscence, and superficial wound infections were observed during the immediate postoperative period. Adverse reactions to the surgical thread, scar adhesion, and superficial wound infection were the most frequent complications during the late postoperative period. Such complications were transitory and with minimal chances of causing death.